2014
DOI: 10.1177/0025802414526180
|View full text |Cite
|
Sign up to set email alerts
|

Fatal laryngeal oedema in an adult from an air rifle injury, and related ballistics

Abstract: Air guns (air pistols and rifles) are already recognized as being potentially lethal. The diabolo pellet has a calibre of .177 (4.5 mm), a 1250 fps velocity, is high energetic, and is most commonly used in such weapons. In the presented case, the victim sustained an air rifle injury to the neck. The pellet passed through the thyroid cartilage, subsequently causing the extensive laryngeal swelling with haematoma around the pellet channel which fatally obstructed the airway. It is estimated microscopically that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…We cannot specify whether the cases with cardiac lesions described by Milroy et al and Mogni et al were included in Guenther's study. Radojevic et al report in 2014 a fatal laryngeal oedema on a 48-year-old man, after a neck shot using an air rifle [7]. In 2020, Dumencic et al report a 9-years-old boy who died after being shot with an air gun; autopsy revealed an entrance gunshot wound on the left lateral side of chest, through the left lung, heart and diaphragm, and a pointed lead pellet (caliber 4.5 mm) was found deep in the liver [8].…”
Section: Discussionmentioning
confidence: 99%
“…We cannot specify whether the cases with cardiac lesions described by Milroy et al and Mogni et al were included in Guenther's study. Radojevic et al report in 2014 a fatal laryngeal oedema on a 48-year-old man, after a neck shot using an air rifle [7]. In 2020, Dumencic et al report a 9-years-old boy who died after being shot with an air gun; autopsy revealed an entrance gunshot wound on the left lateral side of chest, through the left lung, heart and diaphragm, and a pointed lead pellet (caliber 4.5 mm) was found deep in the liver [8].…”
Section: Discussionmentioning
confidence: 99%
“…4 Various compressed air firearm related fatalities have happened with damage to the head, face and neck. [5][6][7] There have additionally been recorded lethal wounds to the thorax and major vessels, including an instance of suicide, wherein an air rifle pellet entered the right ventricle. 8 Intra-abdominal damage has likewise been accounted for in the writing and has been overseen both operatively and non-operatively.…”
Section: Discussionmentioning
confidence: 99%